Prevalence of Revalence of Musculoskeletal Problems Among Manual Handling Workers In Courier Service Industry - Mohd Shahril, Abu Hanifah (Penerbit Universiti Malaysia Pahang, 2015)
Manual handling workers are exposed to various haza rds such as ergonomic. Exposure to ergonomic hazards poses several health effects to w orkers especially to the musculoskeletal system including aches, pain or discomfort on neck, elbow, wrist, upper back, lower back, hip/thigh, knees or feet. The main objective of this study was to deter mine the prevalence of musculoskeletal problems among manual handling workers in courier service in dustry. A cross-sectional study was conducted involving 79 workers in a courier service provider that located in Selangor. Socio-demographic information, job characteristics and musculoskeleta l symptoms for the past 7 days and 12 months were collected by using self-administered questionnaire adapted from Nordic Standardized Questionnaire. Prevalence of musculoskeletal symptoms among manual handling workers is 69.6 %. The most common site of musculoskeletal problems among manual handl ing workers is lower back followed by upper back. Bivariate analysis showed significant associations between education level and duration of employment with musculoskeletal. Preventive and control action should be taken to control the risk factors. This is crucial as musculoskeletal problems can give negati ve impact to workers’ quality of lives, lost time o f work due to absenteeism, reduction of employees’ pr oductivity and increase medical compensation